Optimalisasi Peran Mahasiswa Kkn Dalam Bidang Peningkatan Pendidikan Di Desa Kangkung - Risma Sintiya Dewi; Pramita Khanifatul; Muhammad Akhdan; Den Ayu; Elinda Novita Dewi; Midian Savella; Herxi Thovan; Kasmuri Kasmuri (Lembaga Pengembangan Kinerja Dosen, 2024)
Education is a crucial element in developing an individual's potential and intelligence. To carry out education effectively, teachers are needed who can teach in both formal and non-formal contexts. Our Community Service Program (KKN) was conducted in Kangkung Village, Kangkung District, with the main objective of providing community service and supporting the improvement of children's education in the village. Although the enthusiasm and learning spirit of the children in Kangkung Village is very high, the shortage of teaching staff is a major obstacle in achieving maximum education. This article is entitled